32nd Thermophysics Conference 1997
DOI: 10.2514/6.1997-2569
|View full text |Cite
|
Sign up to set email alerts
|

Transition effects on heating in the wake of a blunt body

Abstract: A series of aerodynamic heating tests was conducted on a 70-deg sphere-cone planetary entry vehicle model in a Mach 10 perfect-gas wind tunnel at freestream Reynolds numbers based on diameter of 8.23x10 4 to 3.15x10 5 . Surface heating distributions were determined from temperature time-histories measured on the model and on its support sting using thin-film resistance gages. The experimental heating data were compared to computations made using an axisymmetric/2D, laminar, perfect-gas Navier-Stokes solver. Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This is caused by the formation of two counter-rotating vortices in the ake. The formation of several vortices in the wake is often observed for high values of the Reynolds number [5,14]. In the present cases, the complexity of the flow in the recirculation and of the wall distributions makes it difficult to quantify the effect of L and α on the heat flux and C p .…”
Section: Heat Flux and C P Distributions On The Aft Of Cylindersmentioning
confidence: 84%
See 1 more Smart Citation
“…This is caused by the formation of two counter-rotating vortices in the ake. The formation of several vortices in the wake is often observed for high values of the Reynolds number [5,14]. In the present cases, the complexity of the flow in the recirculation and of the wall distributions makes it difficult to quantify the effect of L and α on the heat flux and C p .…”
Section: Heat Flux and C P Distributions On The Aft Of Cylindersmentioning
confidence: 84%
“…Detached flow with solid reattachment is mainly observed behind backward facing steps, where the boundary layer detaches at the edge of the step and reattaches on the wall downwind (figure 6). The recompression caused by the reattachment results in a heat flux peak near the reattachment point R S that can reach up to 18 % of the stagnation point heat flux [6,13,14].…”
Section: Wall Heat Flux and Pressure Coefficient In The Shadow Region Of Space Debrismentioning
confidence: 99%
“…Finally, the non-dimensional heat flux along the vehicle surface is shown in Figure 44. With comparisons to numerical results obtained by Scalabrin (2007) and the NEQ2D code (Hollis and Perkins, 1997) and experimental results from the HYPULSE experiments (Hollis, 1996). A small oscillation in the heat flux is present at the location corresponding to the change in the blocking structure of the mesh, but the predicted distribution agrees much better with the experimental results than the other numerical references, in particular, at the extremity of the heat shield.…”
Section: Resultsmentioning
confidence: 99%
“…The Reynolds number at these flow conditions was low enough for the flow along the wedge to be considered laminar according to the criterion of Lees [4], although several previous studies on hypersonic laminar separated flows [5][6][7] have indicated that laminar separated flows readily transition in the free shear layer. The visualisations presented later in the paper showed no evidence of large-scale turbulent structures in the free shear layer.…”
Section: Experiments 21 Facility Flow Conditions and Modelmentioning
confidence: 99%